2017
DOI: 10.1002/slct.201701160
|View full text |Cite
|
Sign up to set email alerts
|

The First Example of Bisindole‐Based Polyurethane Dendrimers: Synthesis and Performance in DSSC

Abstract: A new B3‐type blocked isocyanate core and AB2‐type building block molecules containing bis‐indole moiety were synthesized via a scalable synthetic routes. Starting with these molecules, amine‐ and blocked isocyanate‐terminated polyurethane dendrimers up to third generation were build‐up using (i) a simple urethane interchange reaction, (ii) deprotection of amine and (iii) efficient conversion of amine into blocked isocyanate groups. The structural integrity of the core, building block and their intermediates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Following these pioneering works, a few more dendritic polyurethanes have been reported [39][40][41][42][43][44][45][46]. More recently, Nasar and coworkers have reported the synthesis of hyperbranched polyurethanes and polyurethane dendrimers based on blocked isocyanate chemistry [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Following these pioneering works, a few more dendritic polyurethanes have been reported [39][40][41][42][43][44][45][46]. More recently, Nasar and coworkers have reported the synthesis of hyperbranched polyurethanes and polyurethane dendrimers based on blocked isocyanate chemistry [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46] Recently, Nasar and coworkers have reported synthesis of hyperbranched polyurethanes and polyurethane dendrimers based on blocked isocyanate chemistry. [47][48][49][50][51][52] However, the dendrimers have been synthesized equally via well-established convergent and divergent methods; the convergent method involves a small number of reactions per molecule during the coupling and activation dendrons. 53 This provides greater structural control than with divergent protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic version of large variety of polymers have been reported during the last two decades . Polyurethanes are an important class of industrial materials, however their dendrimers are not adequately reported and studied for solar cell applications; only four reports are available which dealing with up to fourth generation dendrimers . The reason lie under the fact that the synthesis involves highly reactive isocyanate groups and thus it requires skilled effort.…”
Section: Introductionmentioning
confidence: 99%
“…The reason lie under the fact that the synthesis involves highly reactive isocyanate groups and thus it requires skilled effort. Recently, we reported bis‐indole based third generation polyurethane dendrimers and its performance in N‐719 dye sensitized solar cell; it yielded PCE of 6.32%. Herein, we report the successful synthesis of fifth generation polyurethane dendrimers with trifluoroacetamide (protected amine), free amine and blocked isocyanate terminal groups and their enhanced performance as dendrimer electrolyte in DSSCs sensitized with N719 dye.…”
Section: Introductionmentioning
confidence: 99%